Administration of DNA Encoding the Interleukin‐27 Gene Augments Antitumour Responses through Non‐adaptive Immunity. (10th September 2015) - Li, Q.; Sato, A.; Shimozato, O.; Shingyoji, M.; Tada, Y.; Tatsumi, K.; Shimada, H.; Hiroshima, K.; Tagawa, M.
Abstract DNA‐mediated immunization of a tumour antigen is a possible immunotherapy for cancer, and interleukin (IL)‐27 has diverse functions in adaptive immunity. In this study, we examined whether IL‐27 DNA administration enhanced antitumour effects in mice vaccinated with DNA encoding a putative tumour antigen, β‐galactosidase (β‐gal). An intramuscular injection of cardiotoxin before DNA administration facilitated the exogenous gene expression. In mice received β‐gal and IL‐27 DNA, growth of β‐gal‐positive P815 tumours was retarded and survival of the mice was prolonged. Development of β‐gal‐positive Colon 26 tumours was suppressed by vaccination of β‐gal DNA and further inhibited by additional IL‐27 DNA administration or IL‐12 family cytokines. Nevertheless, a population of β‐gal‐specific CD8+ T cells did not increase, and production of anti‐β‐gal antibody was not enhanced by IL‐27 DNA administration. Spleen cells from mice bearing IL‐27‐expressing Colon 26 tumours showed greater YAC‐1‐targeted cytotoxicity although CD3−/DX5+ natural killer (NK) cell numbers remained unchanged. Recombinant IL‐27 enhanced YAC‐1‐targeted cytotoxicity of IL‐2‐primed splenic NK cells and augmented a phosphorylation of signal transducer and activator of transcription 3 and an expression of perforin. These data collectively indicate that IL‐27 DNA administration activates NK cells and augments vaccination effects of DNA encoding a tumour antigen through non‐adaptive immune responses.